Intercorrelation between Digitalization and Women Empowerment (British Journal of Multidisciplinary and Advanced Studies, 2022)
Empowering women throughout the world, is prime objective for all governing enhanced life standards beneficial for humanity. A woman is abbreviated as “Shakti Swaroopa” in Indian Vedic culture having the power of reproduction and multi-oriented behavior. In current scenario, digitalization has affected every core of human world having especial emphasis on women empowerment. The current article explored about digital transformation in field of education, law enforcement system, banking, finance, health care departments depicting its role to women empowerment in all concerned areas. However, some negative impacts of digitalization are also discussed in order to aware women for its safe and secure utilization. Thus, the role of digitalization especially to women empowerment envisioned positive progressive outcomes at various stages of human life governing modern outlook of society worldwide.
Keywords: digitalization; women empowerment; education; technology